Lower limb perfusion scintigraphy with 99mTc-MIBI scintigraphy and determination of endothelin in diabetic and nondiabetic patients - Manevska, Nevena; Stojanoski, Sinisa; Ahmeti, Irfan; Tripunoski, Toni; Pop Gjorceva, Daniela; Majstorov, Venjamin; Pemovska, Gordana (Vojnosanitetski pregled, 2021)
Background/Aim. Peripheral artery disease (PAD) is a common macrovascular complication in patients with diabetes mellitus (DM) as a result of impairment of homeostatic mechanisms of the endothelium, thus initiating the process of atherosclerosis. The imbalance between endothelium-derived vasodilators and vasoconstrictors plays an important role in the pathogenesis of diabetic microangiopathy, as well as in other vascular complications in diabetes. Perfusion scintigraphy using technetium-99m-methoxyisobutyl isonitrile (99mTc-MIBI) can be very useful method for evaluation of the lower limbs muscle perfusion. The aim of this study was: to compare the results of dynamic and static studies of lower limbs tissue muscle perfusion scintigraphy with 99mTc-MIBI (one-day rest-stress protocol) in patients with and without DM and to determine the perfusion reserve for diagnostic evaluation of PAD in patients with DM type 2, as well as to assess the endothelin-1 (ET-1) levels as a vasoconstrictor agent in patients with and without diabetes. Methods. Prospective study was performed in 90 patients, divided into two groups according to the presence of DM – patients with DM type 2 (DP), 60/90 (67%), and patients without DM (NDP), 30/90 (33%). Lower limbs tissue muscle perfusion scintigraphy was done with 99mTc-MIBI including two studies (“rest” and “stress”). Results. In the DP group significantly lower pick of radioactivity was detected in comparison with the NDP group, in both phases (rest and stress), for both calves. Lower counts from the static phase were registered in the region of both calves. Lower inter-extremity indexes as well as perfusion reserve were found in the DP group. There was a significant difference in concentrations of ET-1 between groups (higher concentrations were found in tzhe DP group). Conclusion. This one-day protocol (rest-stress with 99mTc-MIBI) of perfusion scintigraphy of lower limbs is considered a useful procedure in PAD assessment in patients with DM type 2, especially the asymptomatic form.